The distributional effects of fiscal reforms since 1997. - Bond, S; Wakefield, M (IFS, 2003)
The aim of this chapter is to gain a deeper understanding of how tax and benefit reforms have affected different groups in the population. The discussion will also cover the issue of how the burden of ‘taxes on businesses’ has changed. But, in considering this, it is important to remember that individuals ultimately pay all taxes. So our main focus is how the reforms have affected people at different points in the income distribution.